PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN JERSEY AWA SPORTS - Yulfa Rizky; Fenny B.N.L Tobing; Nenny Anggraini (Universitas Kristen Indonesia, 2026)
ABSTRACT Yulfa Rizky, The Influence of Price and Promotion on Purchase Decisions for AWA Sports Jerseys The process of weighing and choosing multiple options according to certain preferences, then deciding on the one deemed most advantageous, is the purchasing decision. Price and marketing are two of the many elements that affect the choice to buy. Fifty male and female members of Universitas Kristen Indonesia's UKOM football and futsal teams participate in this quantitative study. The purpose of this research is to understand how consumer decisions to purchase AWA Sports jerseys are determined by price and marketing. The questionnaire was used as a data collection instrument. To analyze the data, multiple regression analysis was employed.According to the study's findings, the price variable (X1) has a significance level of 0.001, which is less than 0.05, indicating that price significantly and positively suggests consumers' purchasing decisions. Conversely, the work discipline variable (X2) has a significance level of 0.017, which is less than 0.05, indicating that promotion significantly and positively suggests consumers' purchasing decisions.Price and promotion both have a positive and significant impact on purchasing decisions simultaneously, based on the calculated f-value of 14.185 and a significance value of 0.000, both less than 0.005. The modified R2 coefficient value of 0.893 (89.3%) indicates that price and promotion have an impact on consumer purchasing decisions.